Alzheimer’s Disease: Drug Discovery 2020
DOI: 10.36255/exonpublications.alzheimersdisease.2020.ch12
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products for Neurocognitive Disorders

Abstract: Neurocognitive disorders are devastating. In 2016, 43.8 million people were estimated to have Alzheimer' s disease worldwide. By 2050, this figure is expected to rise by 56%. Despite the extreme importance of the disease, the weapons available to us to combat it are very scarce. Natural substances may be a worthwhile option for the treatment and management of neurocognitive disorders. Some of these natural products have been shown to be capable of positively impacting memory, behavior, and functions of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
0
0
Order By: Relevance
“…It is also worth noting that the pharmacological and toxicological effects of curcumin are dose-dependent, and high doses may produce toxic and carcinogenic effects [306] as well as pro-oxidant effects [307]. Other reported side effects include mild nausea and diarrhea, and it can chelate iron and suppress hepcidin, leading to subclinical iron deficiency [308,309]. Additionally, a study using human hepatoma G2 cells found that curcumin had no mutagenic effect at a low concentration of 2.5 µg/mL, but it caused DNA damage in a dose-dependent manner at higher concentrations (10-40 µg/mL) [13].…”
Section: Zingiberaceae Family In Clinical and Toxicity Studymentioning
confidence: 99%
“…It is also worth noting that the pharmacological and toxicological effects of curcumin are dose-dependent, and high doses may produce toxic and carcinogenic effects [306] as well as pro-oxidant effects [307]. Other reported side effects include mild nausea and diarrhea, and it can chelate iron and suppress hepcidin, leading to subclinical iron deficiency [308,309]. Additionally, a study using human hepatoma G2 cells found that curcumin had no mutagenic effect at a low concentration of 2.5 µg/mL, but it caused DNA damage in a dose-dependent manner at higher concentrations (10-40 µg/mL) [13].…”
Section: Zingiberaceae Family In Clinical and Toxicity Studymentioning
confidence: 99%